Building Adaptive Workforces: HRM and Digital Competency in Tourism Innovation - Roslina Alam (Global Review of Tourism and Social Sciences, 2025)
This study investigates the influence of high-involvement HRM (HI-HRM) practices on innovative work behavior (IWB) in Indonesia's tourism sector, focusing on functional flexibility (FF) as a mediator and digital competency as a moderator. Grounded in the Ability-Motivation-Opportunity (AMO) framework, it explores how ability-enhancing, motivation-enhancing, and opportunity-enhancing HR practices shape employee adaptability and innovation. A quantitative approach was employed, collecting data from 300 employees across various tourism segments, with analysis conducted using structural equation modeling. Results confirm that HI-HRM practices positively affect IWB through FF, while digital competency significantly strengthens these relationships. The study provides both theoretical contributions by integrating digital competency into the HRM framework and practical implications for enhancing workforce innovation in the rapidly evolving tourism industry. Managers are encouraged to implement comprehensive HRM strategies and prioritize digital skills training to foster adaptability and maintain competitiveness in Indonesia's dynamic tourism landscape.